Blood Relationship As A Ground Of Inheritance Under Islamic Law - Ibrahim, Ahmad (Journal of Malaysian and Comparative Law, 1979)
Except for marriage and maternal relatives in the Sunni law, rights of inheritance depend upon the relationship between the deceased and the claimant, whether immediate or through any number of intermediate links, being a legitimate relationship.